Contribution and Relevance of Imam Abu Hanifah and Zayd bin Ali's Thinking on Contemporary Online Business Practices - Ayis Mukholik (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2022)
This article discusses legal studies on consumer protection for the circulation of expired food. This is because often found in many stores there are some items that have expired. Juridically, the distribution of expired food is against the laws and regulations. Law Number 8 of 1999 concerning Consumer Protection mandates that “business actors are prohibited from producing and/or trading goods and/or services that do not include the date. The provisions of this law, in addition to providing rights to consumers to obtain valid information on the goods to be purchased, have also prohibited business actors from trading expired goods.